Superficial veins of the forearm: Anatomical-surgical study oriented to angioacces for chronic hemodialysis - Varela, Daniel; Regules, Elías; Ruiz, Claudio; Rudnitzky, Omar; Crestanello, Francisco (Cirugía del Uruguay, 1992)
This 1s a prospective anatomical study of superficial veins of the forearms of 70 human corpses. The statistical analysis of the results tries to establish morphological features of these veins that do not appear in classical anatomical descriptions and condition their utility for the realization of accesses for chronic hemodialysis